2016
DOI: 10.1074/jbc.m116.718395
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Mineralocorticoid Receptor Ligand Binding Domain Impairs Receptor Activation and Has a Dominant Negative Effect over Non-phosphorylated Receptors

Abstract: Post-translational modification of steroid receptors allows fine-tuning different properties of this family of proteins, including stability, activation, or interaction with co-regulators. Recently, a novel effect of phosphorylation on steroid receptor biology was described. Phosphorylation of human mineralocorticoid receptor (MR) on Ser-843, a residue placed on the ligand binding domain, lowers affinity for agonists, producing inhibition of gene transactivation. We now show that MR inhibition by phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Figure 5 also shows the α-helices on the MR as determined by X-ray crystallography (Bledsoe et al 2005, Fagart et al 2005, Edman et al 2015 and amino acids that have been found to be important in either steroid binding or transcriptional activation of the MR or CR (Fagart et al 1998, Geller et al 2000, Bledsoe et al 2005, Hultman et al 2005, Bridgham et al 2006, Shibata et al 2013, Edman et al 2015, Jimenez-Canino et al 2016, Mani et al 2016 or the GR (Bledsoe et al 2002, He et al 2014, Edman et al 2015, Mani et al 2016. A striking feature, discussed in more detail below, is the strong conservation of amino acids among the CR, MR, GR, PR and AR, including lamprey PR and CR.…”
Section: Lldsmhdlvsdllefcfytfreshalkvefpamlveiisdqlpkvesgnakplyfhrkmentioning
confidence: 98%
See 2 more Smart Citations
“…Figure 5 also shows the α-helices on the MR as determined by X-ray crystallography (Bledsoe et al 2005, Fagart et al 2005, Edman et al 2015 and amino acids that have been found to be important in either steroid binding or transcriptional activation of the MR or CR (Fagart et al 1998, Geller et al 2000, Bledsoe et al 2005, Hultman et al 2005, Bridgham et al 2006, Shibata et al 2013, Edman et al 2015, Jimenez-Canino et al 2016, Mani et al 2016 or the GR (Bledsoe et al 2002, He et al 2014, Edman et al 2015, Mani et al 2016. A striking feature, discussed in more detail below, is the strong conservation of amino acids among the CR, MR, GR, PR and AR, including lamprey PR and CR.…”
Section: Lldsmhdlvsdllefcfytfreshalkvefpamlveiisdqlpkvesgnakplyfhrkmentioning
confidence: 98%
“…However, because intercalated cells lack 11β-HSD2, activation of the intercalated cell MR by de-phosphorylation is followed by F or B acting as an MR agonist (Funder 2013, Shibata et al 2013. Interestingly, high potassium levels increase phosphorylation of Ser-843 (Funder 2013, Shibata et al 2013, Jimenez-Canino et al 2016. Phosphorylated Ser-843 human MR has only been found in intercalated cells in the kidney distal tubule; other tissues such as brain, aorta, heart and colon do not contain phosphorylated Ser-843.…”
Section: Phosphorylation Of Ser-843 Inactivates Human Mrmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain a deeper understanding of the evolution of the MR, we have taken advantage of the sequencing, in the last five years, of a cornucopia of genomes from vertebrates at key evolutionary transitions, including lamprey, elephant shark and coelacanth, to investigate regions of conservation and divergence among and between MRs and GRs. We use these sequence analyses, the crystal structures human MR (Bledsoe, et al 2005;Edman, et al 2015;Fagart, et al 2005;) and GR (Bledsoe, et al 2002;He, et al 2014) and functional studies of human MR mutants (Bledsoe et al 2005;Fagart, et al 1998;Geller et al 2000;Jimenez-Canino, et al 2016;Li et al 2005;Shibata, et al 2013,Mani, 2016 to investigate the evolution of selectivity for Aldo and other corticosteroids by the MR in terrestrial vertebrates (Baker et al 2013) and ray-finned fish (Arterbery, et al 2011;Bury and Sturm 2007;Prunet, et al 2006;Sugimoto et al 2016), as well as the basis for binding of some glucocorticoids by human MR and other vertebrate MRs Mani et al 2016). Together these data provide molecular and structural fingerprints for investigating the evolution of selectivity for 3ketosteroids by the MR in vertebrates.…”
Section: Figure 3 Pathway For Synthesis Of Aldosterone From Progestermentioning
confidence: 99%
“…Interestingly, high potassium levels increase phosphorylation of Ser-843 (Funder 2013;Jimenez-Canino et al 2016;Shibata et al 2013 phosphorylated in vivo, then the evolution of a corresponding proline in the GR lobe-finned and ray-finned fishes would provide a mechanism for specificity for regulation of transcriptional activation of the MR through a kinase/phosphatase that would not affect the GR.…”
Section: Phosphorylation Of Ser-843 Inactivates Human Mrmentioning
confidence: 99%